2018
DOI: 10.1530/eje-17-0589
|View full text |Cite
|
Sign up to set email alerts
|

Time to parathyroid function recovery in patients with protracted hypoparathyroidism after total thyroidectomy

Abstract: Permanent hypoparathyroidism should not be diagnosed in patients requiring replacement therapy for more than six months, especially if the four parathyroid glands were preserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 20 publications
8
55
1
1
Order By: Relevance
“…Hypoparathyroidism is one of the most common complications after total thyroidectomy. Some studies have found that calcium and calcitriol supplementation can aid the recovery of parathyroid function in patients with hypoparathyroidism [7,[12][13][14]. In agreement with previous ndings [13,15], in the present study, parathyroid function in most patients returned to normal within 1 month (87.39%) after the operation, and intraoperative PGRIS scores was an independent in uencing factor for the return of normal PTH after surgery.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Hypoparathyroidism is one of the most common complications after total thyroidectomy. Some studies have found that calcium and calcitriol supplementation can aid the recovery of parathyroid function in patients with hypoparathyroidism [7,[12][13][14]. In agreement with previous ndings [13,15], in the present study, parathyroid function in most patients returned to normal within 1 month (87.39%) after the operation, and intraoperative PGRIS scores was an independent in uencing factor for the return of normal PTH after surgery.…”
Section: Resultssupporting
confidence: 92%
“…The predictive effect of rapid biochemical indicators on parathyroid function will be helpful for clinicians to diagnose and better manage the dosage of calcium tablets and calcitriol in patients. In addition, many scholars have explored the predictive effect of short-term PTH after thyroid surgery [6][7][8][9]. However, many junior hospitals do not have the equipment to detect PTH, or the test is too time-consuming.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also implies that the possibility of parathyroid gland revascularization after the wound is closed is not considered. This is not consistent with the fact that recovery of the parathyroid function is a dynamic, long-standing process [40]. In addition, interpretation of the parathyroid function data in this study is hampered because four glands were identified in only 4/36 patients and all subjects received routine calcium and vitamin D supplementation after thyroidectomy.…”
Section: The Psychological Variables: Color Change Angiography and Scontrasting
confidence: 74%
“…For this cross-sectional survey, patients were selected from our database. Although RFA and surgery had been carried out at different times before the survey, we made sure that all patients had been treated at least one year prior to it, as postsurgical complications might need one year to recover [38]. Certainly, in some patients survey point was far from initial surgery, which should be taken into account when looking at our data.…”
Section: Discussionmentioning
confidence: 99%